Dectin-1 is required for miR155 upregulation in murine macrophages in response to Candida albicans. Issue 1 (2nd January 2017) - Agustinho, Daniel Paiva; de Oliveira, Marco Antônio; Tavares, Aldo Henrique; Derengowski, Lorena; Stolz, Valentina; Guilhelmelli, Fernanda; Mortari, Márcia Renata; Kuchler, Karl; Silva-Pereira, Ildinete
ABSTRACT: The commensal fungal pathogen Candida albicans is a leading cause of lethal systemic infections in immunocompromised patients. One of the main mechanisms of host immune evasion and virulence by this pathogen is the switch from yeast form to hyphal growth morphologies. Micro RNAs (miRNAs), a small regulatory non-coding RNA, has been identified as an important part of the immune response to a wide variety of pathogens. In general, miRNAs act by modulating the intensity of inflammatory responses. miRNAs act by base-paring binding to specific sequences of target mRNAs, generally causing their silencing through mRNA degradation or translational repression. To study the impact of C. albicans cell morphology upon host miRNA expression, we investigated the differential modulation of 9 different immune response-related miRNAs in primary murine bone marrow-derived macrophages (BMDMs) exposed to either yeasts or hyphal forms of Candida albicans . Here, we show that the different growth morphologies induce distinct miRNA expression patterns in BMDMs. Interestingly, our data suggest that the C-Type lectin receptor Dectin-1 is a major PRR that orchestrates miR155 upregulation in a Syk-dependent manner. Our results suggest that PRR-mediating signaling events are key drivers of miRNA-mediated gene regulation during fungal pathogenesis.